MENCIPTAKAN SMART ASN MENUJU 4.0 DI KANTOR CAMAT KECAMATAN SITINJAU LAUT KABUPATEN KERINCI: PEBI JULIANTO - PEBI JULIANTO, S.Sos., MM., CHt (LPPM STIA Nusantara Sakti, 2021)
This study aims to determine SMART ASN Towards 4.0 in the Apparatus of Sitinjau Laut District, Kerinci. This study uses a descriptive qualitative research method with in-depth interview approach using interview guidelines with the problem under study and documentation. From the results of data analysis, it can be concluded that to determine the quality of SMART ASN Towards 4.0 at the Sitinjau Laut District Office at this time, researchers used six dimensions of quality SMART ASN Towards 4.0, namely Recruitment of Prospective Civil Servants (CPNS) using Computer Assisted Test (CAT), Development career patterns, competency development, career development, promotion through open selection, and succession plans in creating SMART ASN Towards 4.0 at the Sitinjau Laut sub-district office. Government tasks are carried out in the context of carrying out general government functions which include the empowerment of institutions, personnel, and administration. Meanwhile, certain development tasks are carried out through economic and social development aimed at increasing the welfare and prosperity of the entire community.